2018
DOI: 10.3171/2016.10.jns16747
|View full text |Cite
|
Sign up to set email alerts
|

A proposed plan for personalized radiosurgery in patients with trigeminal neuralgia

Abstract: OBJECTIVE During the last 25 years, more than 100,000 patients worldwide with trigeminal neuralgia (TN) have undergone stereotactic radiosurgery (SRS) with a standard dose of radiation. However, the radiobiological effect of radiation is determined by the amount of energy delivered to the tissue (integral dose [ID] = mean dose × target volume) and is directly associated with the nerve volume. Although the trigeminal nerve volume varies among patients with TN, the clinical impact of this variation in delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The ID is the product of the mean dose and the target nerve volume and therefore represents an ideal parameter for non-isocentric treatments in which not only the dose, but also the target volume can be modulated to fit individual anatomy and clinical objectives. Mousavi et al [23] investigated 155 patients treated by GKS and reported that the optimal treatment outcome could be achieved by medium IDs (1.4-2.7 mJ). To be able to compare our cohort with the study by Mousavi et al [23], we categorized the ID in the same way and observed that the patients with lower IDs (i.e.…”
Section: Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ID is the product of the mean dose and the target nerve volume and therefore represents an ideal parameter for non-isocentric treatments in which not only the dose, but also the target volume can be modulated to fit individual anatomy and clinical objectives. Mousavi et al [23] investigated 155 patients treated by GKS and reported that the optimal treatment outcome could be achieved by medium IDs (1.4-2.7 mJ). To be able to compare our cohort with the study by Mousavi et al [23], we categorized the ID in the same way and observed that the patients with lower IDs (i.e.…”
Section: Key Resultsmentioning
confidence: 99%
“…Mousavi et al [23] investigated 155 patients treated by GKS and reported that the optimal treatment outcome could be achieved by medium IDs (1.4-2.7 mJ). To be able to compare our cohort with the study by Mousavi et al [23], we categorized the ID in the same way and observed that the patients with lower IDs (i.e. < 1.4 mJ) were more likely to suffer pain relapse.…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose exposure of the adjacent brainstem is a critical factor in repeat SRS and related to post procedure facial numbness [ 45 ]. The total cumulative dose to the brainstem and cumulative doses to adjacent structures such as the temporal lobe must be carefully calculated [ 46 , 47 ]. Normally, the initial SRS dose with either GK or SRS varies between 70 to 90 Gy with most centers using a dose of 75 Gy [ 1 , 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…The higher dose, both for initial and repeat treatment, is associated with a higher incidence of residual facial numbness varying from 12 to 30% [ 1 , 5 , 13 , 14 ]. There are reports of even third SRS treatments and a more individualized plan, especially targeting sections of the trigeminal nerve not in the original radiation plan in cases with recurrent pain [ 42 , 47 , 48 ]. Experience with treating multiple brain metastatic disease clearly demonstrates the feasibility of multiple repeat SRS treatments [ 49 ].…”
Section: Reviewmentioning
confidence: 99%